The Effect of Marketing Mix on Consumer Loyalty at Alfamart Lengkong - Sarah Fadila; Layaman Layaman (Cirebon International Journal of Economics and Business, 2023)
The marketing mix refers to a series of actions or strategies used by a company consisting of product, price, promotion and place to build and market products to customers and them determine the level of marketing succes to get the desired response from the target market. Consumer loyalty is the result of companies offering benefits to customers so that they make repeat purchases or continue to make more purchases. The purpose of this study was to determine wheter the marketing mix includes product, price, promotion and place has an effect on consumer loyalty at Alfamart Lengkong, Sindangwangi – Majalengka. The sampling method for this survey used accidental sampling, all consumers of Alfamart Lengkong were found radomly and met the requirements as respondents, and the analytical method was used multiple linear regression analysis. The result of this study indicate that product, promotion and place partially have a significant effect on consumer loyalty while price has no significant effect. The variabels of product, price, promotion and place simultaneously have a significant effect on consumer loyalty. Given the weak effect of price on consumer loyalty, management must pay attention in the company’s marketing plan.